Post Mortem Examination and Autopsy - Current Issues From Death to Laboratory Analysis 2018
DOI: 10.5772/intechopen.71182
|View full text |Cite
|
Sign up to set email alerts
|

Application of CO-oximeter for Forensic Samples

Abstract: CO-oximeter is routinely used in clinical practice, and it has been applied in the ield of forensic medicine. It is a simultaneous and nondestructive technique for the analysis of total hemoglobin (Hb) and various Hb species, such as oxyhemoglobin, reduced hemoglobin, carboxyhemoglobin, and methemoglobin. It automatically measures the proportion of each species of Hb and oxygen contents. This is an easy, rapid, and convenient way as the laboratory test. Since there are many advantages such as no necessity of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…For instance, the forensic pathologist might retrieve the pacemaker data from a deceased person to determine or exclude causes of death as well as to estimate the PMI [11]. Data from connected biosensors such as oximeters [12], blood glucometers [13], or electrochemical sensors [14] might also be exploited in the future as complementary elements to determine the cause of death. Moreover, observational data from non-medical people may be used for forensic diagnosis.…”
Section: Ai and Disease Categories: Redefining Discovering And Strati...mentioning
confidence: 99%
“…For instance, the forensic pathologist might retrieve the pacemaker data from a deceased person to determine or exclude causes of death as well as to estimate the PMI [11]. Data from connected biosensors such as oximeters [12], blood glucometers [13], or electrochemical sensors [14] might also be exploited in the future as complementary elements to determine the cause of death. Moreover, observational data from non-medical people may be used for forensic diagnosis.…”
Section: Ai and Disease Categories: Redefining Discovering And Strati...mentioning
confidence: 99%
“…It has been reported that acceptable blood levels for both MetHb and COHb are 2%. 135 The effect of the variability in MetHb or COHb blood levels was studied (as shown in Fig. 7e).…”
Section: Bilirubin Spectroscopymentioning
confidence: 99%